Assessment of barriers to the dietary adherence among type 2 diabetic patients in Pakistan: a cross-sectional study - Shabbir, Sukaina; Amer, Mehreen; Mughal, Saba; Rashid, Thamina; Habiba (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the common barriers responsible for non-adherence to dietary recommendations among type 2 diabetic patients. Method: The cross-sectional study was conducted from October 4, 2021, to March 6, 2022, at the National Institute of Diabetes and Endocrinology, Dow University of Health Sciences, Karachi, and comprised type 2 diabetes patients of either gender aged 18-80 years who had previously been given recommended dietary advice. Dietary barriers were assessed using a 27-item validated questionnaire, and the subjects were compared in terms of age and diabetes duration. Anthropometric measurements and laboratory parameters were also measured. Data were analysed using Stata 17. Results: Of the 312 subjects, 234(75%) were females. The overall mean age was 52.2±11.2 years, and mean body mass index was 27.2±5.5kg/m2. The reliability of the questionnaire was established with Cronbach’s alpha 0.89. Factor analysis yielded 8 common barriers; lack of knowledge about dietary recommendations (variance: 14.7%), situational barrier (variance: 10.7%), lack of family support (variance: 9.5%), stress-related eating problems (variance: 9.1%), boring and monotonous diet (variance: 8.0%), expensive and ineffective diet recommended (variance: 6.5%), work conditions/don’t like food in diet (variance: 5.5%), and feeling hungry and weak (variance: 5.4%). The total variation explained by all the 8 factors was 69.4%. Conclusion: Lack of knowledge regarding dietary recommendations was reported to be the most common barrier towards recommended dietary adherence. Key Words: Diabetes mellitus, Type 2 diabetes, Dietary adherence, Barriers, Non-adherence, Dietary advice.